Hydrogenase and ribulose diphosphate carboxylase during autotrophic, heterotrophic, and mixotrophic growth of scotochromogenic mycobacteria. - Park, S S (1976)
Two key autotrophic enzyme systems, hydrogenase and ribulose diphosphate carboxylase, were examined in Mycobacterium gordonae and two other chemolithotrophic, scotochromogenic mycobacteria under different cultural conditions. In all three organisms both enzymes were inducible and were produced in significant levels only in the presence of the specific substrate, hydrogen or carbon dioxide. M. gordonae exhibited increased growth rates and yields, indicating mixotrophic growth, in the presence of a number of single organic substrates, including acetate, pyruvate, glucose, fructose, and glycerol. In contrast to other aerobic hydrogen autotrophs, the presence of either acetate or pyruvate did not repress ribulose diphosphate carboxylase, and mixotrophic growth was rapid with these substrates. In the absence of carbon dioxide, growth in glycerol medium under an atmosphere of hydrogen and oxygen was severely inhibited, even with cells preadapted to heterotrophic growth on glycerol. Cyclic adenosine monophosphate was not effective in inducing hydrogenase or carboxylase in heterotrophic, mixotrophic, or hydrogen-inhibited cultures.